1991
DOI: 10.1172/jci115279
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and glucose independently regulate the beta-adrenergic receptor-adenylate cyclase system in cardiac myocytes.

Abstract: We explored the effects of two components of ischemia, hypoxia and glucose deprivation, on the jl-adrenergic receptor (fiAR)-adenylate cyclase system in a model of hypoxic injury in cultured neonatal rat ventricular myocytes. After 2 h ofhypoxia in the presence of 5 mM glucose, cell surface #AR density (3H-CGP-12177) decreased from 54.8±8.4 to 39±63 (SE) fmol/mg protein (n = 10, P < 0.025), while cytosolic #AR density ('25I-iodocyanopindolol IICYPI) increased by 74% (n = 5, P < 0.05). Upon reexposure to oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…LDH release from glucose-supplemented myocytes subjected to 2 h of hypoxia and from glucose-deprived myocytes subjected to 30 or 60 min of hypoxia was no different from normoxic control cells (24). These data suggested that hypoxic preconditioning does not cause irreversible cellular damage, an assumption that we verified using a cell viability assay (see below).…”
Section: Methodssupporting
confidence: 68%
See 3 more Smart Citations
“…LDH release from glucose-supplemented myocytes subjected to 2 h of hypoxia and from glucose-deprived myocytes subjected to 30 or 60 min of hypoxia was no different from normoxic control cells (24). These data suggested that hypoxic preconditioning does not cause irreversible cellular damage, an assumption that we verified using a cell viability assay (see below).…”
Section: Methodssupporting
confidence: 68%
“…Lactate Dehydrogenase Assay-The effect of hypoxia on LDH release from cardiac myocytes was assessed as described previously (24). Following each treatment, culture media were stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In congenital heart diseases, cyanosis has been associated with various alterations in cardiac sympathetic activity (1)(2)(3)(4)(5)(6). In acute hypoxemia, for example, stimulation of the sympathetic activity results in increased heart rate and cardiac output as a compensatory mechanism to maintain adequate oxygen supply (7,8), whereas in chronic situations, such as in cyanotic congenital heart disease, several complex events probably contribute toward the mechanism(s) to sustain adequate oxygen supply (9).…”
mentioning
confidence: 99%